Pengaruh Metode Solfeggio Dalcroze terhadap Keterampilan Bermain Angklung di Sekolah Dasar - Dita Amalia; Irna Khaleda Nurmeta; Lutfi Hamdani Maula (Journal on Education, 2025)
This study aims to analyse the effect of the Solfeggio Dalcroze method on student’s angklung playing skills in music learning. The study involved solmization exercises, rhythm and melody listening to enhance students’ musical sensitivity. The method used was experimental with a quasi-experimental approach and a Non-equivalent Control Group Design, involving two groups: the experimental group and the control group, selected non-randomly. The research subject were 30 fourth-grade students at SDN Caringin Ngumbang, Sukabumi. Data were collected through pretest and posttest skill tests. Data analysis was conducted using IBM SPSS Statistic 30, which included validity, reability, normality, homogeneity tests and t-tests. The independent t-test result showed a significance value of 0,001 < 0,05, indicating a significance difference between the experimental and control groups after the treatment. The paired t-test result showed a greater improvement in the experimental group (41,600) compared to the control group (22,600). The findings indicate the implementation of the Solfeggio Dalcroze method significantly affects elementary school students’ angklung playing skills.